2021
DOI: 10.17241/smr.2021.00983
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders During Pregnancy and Postpartum: A Systematic Review

Abstract: This study aimed to asses previous research results about bio-physiological alterations during pregnancy and postpartum, and make clear outlook about prevalence and related factors of sleep disorders during pregnancy and postpartum. In this review, the articles that published from 2000 to 2019 were reviewed. Related articles were searched from databases in English language. After evaluation of inclusion and exclusion criteria, articles were chosen and reviewed based on the University of York strategies. Sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…The ESS has excellent psychometric validity for screening daytime sleepiness in the Ethiopian population [ 31 , 32 ] with a reliability test of 0.725 [ 32 ]. Women with an ESS score >10 were included in the sleepy group, and those with a score ≤10 were included in the non-sleepy group [ 33 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ESS has excellent psychometric validity for screening daytime sleepiness in the Ethiopian population [ 31 , 32 ] with a reliability test of 0.725 [ 32 ]. Women with an ESS score >10 were included in the sleepy group, and those with a score ≤10 were included in the non-sleepy group [ 33 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Penurunan durasi tidur mengakibatkan kondisi ibu hamil menurun, konsentrasi berkurang, mudah lelah, badan terasa pegal, tidak mood bekerja, dan cenderung emosional pada akhirnya menyababkan beban kehamilan menjadi semakin berat (Moghadam et al, 2021). Akibat lanjut gangguan tidur menimbulkan depresi dan stres yang akan berpengaruh pada janin yang dikandungnya.…”
Section: Pendahuluanunclassified
“…The perinatal period is a time characterized by several physical and emotional changes. During the perinatal period several structural, hormonal and other body chemicals were changed [1], as a result, women were highly vulnerable to emotional and psychological conditions such as sleep disturbance, mood, anxiety and others that influence the mother and child's development and health [2,3]. It is also characterized by a decrease in physical structure and strength, a feeling of fatigue, breastfeeding, and role transition, which results in a painful effect on the mothers and their child's health [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep problems in the perinatal period, especially during pregnancy, are common health problems [6,7]. A recent study showed that 76%-97% and 33.2% of women experienced sleep problems in the antenatal and postnatal periods, respectively [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation